2018
DOI: 10.3892/ijo.2018.4655
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑143‑3p suppresses cell growth and invasion in laryngeal squamous cell carcinoma via targeting the k‑Ras/Raf/MEK/ERK signaling pathway

Abstract: MicroRNAs (miRNAs or miRs) have been identified as an important regulator in carcinogenesis and other pathological processes. However, the molecular mechanism underlying the function of miRNAs in the progression and development of laryngeal squamous cell carcinoma (LSCC) remains to be fully elucidated. In the present study, the miRNA expression pattern in LSCC tissues was profiled using miRNA microarray analysis. It was found that a large set of miRNAs are aberrantly expressed in LSCC tissues and that miR-143-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Similarly, microRNA (miR) analysis in LSCC based on specific markers such as miR-143-3p seems to add critical molecular information regarding the K-Ras expression patterns in them. A study group suggested that enhanced miR-143-3p inhibited cell growth and metastasis suppressing the K-Ras/Raf/mitogen-activated protein kinase (MEK)/extracellular signal-regulated kinase (ERK) signalling pathway (17). Co-analyzing epidermal growth factor receptor (EGFR) and K-Ras genes by applying high resolution melting analysis (HRMA) and one-step real-time polymerase chain reaction (PCR), a study group reported a very limited K-Ras mutational rate in the Belgian population with Head and Neck Squamous Cell Carcinoma (HNSCC) including LSCC cases (7% of the specimens, only one case with point mutation) (18).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, microRNA (miR) analysis in LSCC based on specific markers such as miR-143-3p seems to add critical molecular information regarding the K-Ras expression patterns in them. A study group suggested that enhanced miR-143-3p inhibited cell growth and metastasis suppressing the K-Ras/Raf/mitogen-activated protein kinase (MEK)/extracellular signal-regulated kinase (ERK) signalling pathway (17). Co-analyzing epidermal growth factor receptor (EGFR) and K-Ras genes by applying high resolution melting analysis (HRMA) and one-step real-time polymerase chain reaction (PCR), a study group reported a very limited K-Ras mutational rate in the Belgian population with Head and Neck Squamous Cell Carcinoma (HNSCC) including LSCC cases (7% of the specimens, only one case with point mutation) (18).…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis and treatment of LSCC have improved with advancements in therapeutic strategies; the 5-year overall survival rate of patients with LSCC is ~64% ( 5 ). Increasing evidence suggest that miRNAs exert tumor suppressive or oncogenic functions in the progression of LSCC ( 21 , 40 42 ). A previous study reported that miR-375-3p is downregulated in head and neck cancer ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 57 reported that MIR143‐3p exhibits an anti–tumor effect on laryngeal squamous cell carcinoma, the most frequent cancer of the head and neck cancers, by targeting KRAS and its effector MAPK/ERK signaling pathway. In addition, Xu’s group demonstrated that the MIR143 overexpression inhibits the cell growth of nasopharyngeal cancer both in vitro and in vivo 58 .…”
Section: The Role Of Mir143‐3p On Rat Sarcoma Signaling Network In Vmentioning
confidence: 99%